ผลของการจัดกิจกรรมการเล่านิทานเบญจศีลที่มีต่อความมีวินัยในเด็กปฐมวัย - อาภาธโร (สุภาปุ), พระภูพิงค์; เล่ห์มงคล, ปัทมาวดี; หิรัณย์ชโลทร, ปิยะนันท์ (วารสาร ศึกษาศาสตร์ มมร, 2019)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาผลของการจัดกิจกรรมการเล่านิทานเบญจศีลที่มีต่อความมีวินัยในเด็กปฐมวัย กลุ่มเป้าหมายที่ใช้ในการวิจัยครั้งนี้คือ เด็กปฐมวัยชาย-หญิง ที่มีอายุ 5-6 ปี ที่กำลังศึกษาอยู่ในชั้นอนุบาลปีที่ 2 ภาคเรียนที่ 2 ปีการศึกษา 2561 โรงเรียนวัดบรมนิวาส กรุงเทพมหานคร จำนวน 18 คน เครื่องมือที่ใช้ในการวิจัย คือ แผนการจัดกิจกรรมการเล่านิทานเบญจศีล จำนวน 9 แผน แบบสังเกตพฤติกรรมความมีวินัยสำหรับเด็กปฐมวัย และแบบบันทึกพฤติกรรมความมีวินัยสำหรับเด็กปฐมวัย วิเคราะห์ข้อมูลโดยการหาค่าเฉลี่ย ค่าเบี่ยงเบนมาตรฐาน และการวิเคราะห์เชิงเนื้อหา           ผลการวิจัยพบว่า เด็กปฐมวัยที่ได้รับการจัดกิจกรรมการเล่านิทานเบญจศีล มีคะแนนเฉลี่ยความมีวินัยหลังการทดลองสูงกว่าก่อนการทดลอง และเด็กปฐมวัยที่ได้รับการจัดกิจกรรมการเล่านิทานเบญจศีล มีคะแนนเฉลี่ยความมีวินัยต่อสิ่งแวดล้อมหลังการทดลองสูงกว่าวินัยต่อตนเอง และวินัยต่อผู้อื่น   The purpose of this research was to study the effects of the five-precept storytelling activity provision on discipline in young children. Subjects used in this study consisted of 18 male and female young children ranging in age from 5 to 6 years old. They were studying in kindergarten level 2 class in the second semester year of 2019 in Boromniwas school, Bangkok. The research instruments were 9 plans on five-precept storytelling activity provision of young children, observation form on discipline behavior of young children, young children’s discipline behavior records. The obtained data was analyzed by mean, standard deviation, and content analysis.The results of research were young children who engaged in the five-precept tale story telling activity had higher discipline behavior scores than those who did not, young children who participated in the story telling activities had higher discipline towards the environment after the experiment than discipline towards themselves and others.